In Vitro Micropropagation of Aloe adigratana Reynolds Using Offshoot Cuttings - Niguse, Mulu (ScientificWorldJournal, 2020)
This study aimed at developing a suitable and reproducible protocol for in vitro micropropagation of Aloe adigratana Reynolds using explants from offshoots with the help of the most commonly used plant growth regulators (PGRs). Explants were initiated in full-strength Murashige and Skoog (MS) media enriched with 0.2 mg/L benzylaminopurine (BAP) + 0.2 mg/L naphthaleneacetic acid (NAA). Shooting experiment was conducted in full-strength MS media enriched with 0/0, 0.5/0.5, 1.0/0.5, 1.5/0.5, and 2.0/0.5 mg/L BAP/NAA. Likewise, rooting experiment was carried out in half-strength MS media enriched with NAA at 0.5, 1.0, and 1.5 mg/L and indol-3-butyric acid (IBA) at 0.5, 1.0, and 1.5 mg/L. Finally, acclimatization study was conducted in greenhouse, nursery, and open field. The shooting response of the plant was best in MS media enriched with 1.0 mg/L BAP + 0.5 mg/L NAA. This media formulation resulted in the shortest mean number of days to shooting (14.00 ± 2.30 days), the highest mean shoot number (4.00 ± 3.40), and the second highest mean shoot length (8.60 ± 2.10 cm). IBA enhanced rooting at higher concentrations (1.0 and 1.5 mg/L), but NAA did the same at lower concentrations (0.5 and 1.0 mg/L). All plantlets (n = 62) survived primary acclimatization. Secondary acclimatization in composted and matured soil media under nursery and open field (sun light) condition produced 88 to 93% survival rate. The death of plantlets in the secondary acclimatization is accounted to mechanical damage. This study demonstrated that the tested PGRs were useful in enhancing the in vitro micropropagation of the plant. Future studies need to focus on optimizing the protocol for large-scale, commercial micropropagation.